Modelos econométricos na avaliação contingente de uma unidade de conservação urbana com utilização da técnica Delphi e Referendo - Costa, Marcelo Ednan Lopes da (2016)
The valuation of environmental goods and services is an important tool that can assist in making decisions for the definition of public and private policies on the management of goods and services from natural capital, and that is what was found the need for monetary value the Mother State park Bonifacia, located in the city of Cuiaba - MT. The State Park Mother Bonifacia is an Integral Protection Conservation Unit with 77.16 hectares. The park provides various environmental services to society in the form of recreation, leisure and contact with nature, ensuring a better quality of life for people. This study aimed to monetarily assign the environmental value of the State Park Mother Bonifácia through the willingness to pay (WTP) of its regulars for the conservation and improvement of environmental assets, using the contingent valuation method, using the technique referendum approach to monitoring. Bids used in the referendum technique with follow-up were from consulting specialists in the environmental area, this consultation known as the Delphi technique. First set up the mode of interview later realized the calculation of sample size (n) for a confidence level of 95.5%, was then prepared the questionnaire and the interviews with data analysis and interpretation results. Among the attendees, 62% agreed to contribute financially to some value to conserve and improve the environmental quality of the Park. The value estimated by econometric logit model to define the individual WTP of the regulars Park was R$ 3,50 / goer. The annual total monetary value of the environmental services provided by Mother State Park Bonifacia, defined as EVER and calculated by the contingent valuation method is R$ 840.000,00.